"Rischio Sismico e città solidale”: dalla ricostruzione del 1693 all'attualità tra tecniche, prevenzione, paure e speranze. (GEOmedia, 2020)
This paper shortly describes the project started by the Digital Cultural Heritage (DiCultHer) Sicilian Centre in the 2018-2019 school year, to participate in the Week of Digital Cultures in Matera (Italy). The objective of the project, ambitious and still open to contributions, is to produce a digital storytelling of the catastrophic event that marked the fate of a large area of eastern Sicily: the 1693 earthquake. The event caused destruction and death, but it also mobilized an extraordinary solidarity of the population and a demanding reconstruction that led to the baroque architecture that has become a UNESCO World Heritage Site.